2014
DOI: 10.1080/14678802.2014.923151
|View full text |Cite
|
Sign up to set email alerts
|

Does a more participatory approach to reintegrating ex-combatants lead to better outcomes? Evidence from Sierra Leone and Liberia

Abstract: Peace agreements and ceasefires may be signed, but whether they hold is another question. Rather than being single events, they are embedded in a peace process, which often begins long before any signatures are added, and can continue even longer afterwards. Supporting this process, with all the scaffolding required for social, political, institutional and physical reconstruction, is what we now know as peacebuilding. And a key component in that task is dealing with the combatants who took part in the armed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
(5 reference statements)
1
13
0
1
Order By: Relevance
“…Graduation ceremonies and training certificates were provided for participants who completed the programmes (Munive & Jakobsen, 2012). Numerous DDR/RRR graduates experienced re-marginalisation and disappointment once the programmes officially ended (Bøås & Bjørkhaug, 2010; Kilroy, 2014; Maclay & Ozerdem, 2010; McMullin, 2013; Munive & Jakobsen, 2012), similar to post-graduation narratives we encountered in this study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Graduation ceremonies and training certificates were provided for participants who completed the programmes (Munive & Jakobsen, 2012). Numerous DDR/RRR graduates experienced re-marginalisation and disappointment once the programmes officially ended (Bøås & Bjørkhaug, 2010; Kilroy, 2014; Maclay & Ozerdem, 2010; McMullin, 2013; Munive & Jakobsen, 2012), similar to post-graduation narratives we encountered in this study.…”
Section: Discussionsupporting
confidence: 73%
“…Kilroy described the identical understanding of ID cards among graduates from reintegration programmes: “the experience with the identity cards left many ex-combatants with the impression that their benefits were being siphoned off by people working in the agencies” (Kilroy, 2015). Moreover, common to both reintegration programmes and Ebola vaccine research were pre-participatory aspirations of participants; ongoing, temporary social protection during participation; and unmet expectations after graduation, which appeared in stark contrast with the perceived wealth and power absorbed by the implementers (Kilroy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…But these research traditions have not studied the effect of concealing a former combatant identity on their reintegration into civilian life in an ongoing conflict scenario. Many empirical studies in post-conflict scenarios define social reintegration in terms of acceptance of ex-combatants by their families and their neighbours (Gomes Porto, Parsons, & Alden, 2007;Humphreys & Weinstein, 2007;Kilroy, 2014;Nadler & Shnabel, 2015). Although there is no academic consensus on the definition of social reintegration of the ex-combatant (Kaplan & Nussio, 2018), the persistence of the term acceptance in almost all definitions (it is understood that it is acceptance of the ex-combatant -as ex-combatant -by the community) makes it possible to understand that the concealment of the former identity is not a mechanism of integration compatible with the spirit of the process itself.…”
mentioning
confidence: 99%
“…First, to promote peace and reconciliation, since the 1980’s the international community has promoted programs of Disarmament, Demobilization, and Reintegration (DDR) that include skills training to help economic reintegration of ex-combatants, including child soldiers [36]. Unfortunately, multiple studies have shown that reintegration can be threatened by numerous elements such as lack of reconciliation [37], little consideration for local contexts and needs of program recipients [38] and poor participation of recipients in the definition and implementation of the program [39]. Second, it has been argued that education can offer a protective environment for children particularly through emotional, psychological and cognitive development [40, 41] while protecting them from forced recruitments, exploitation and prostitution [6, 42].…”
Section: Introductionmentioning
confidence: 99%